2021
DOI: 10.3390/antibiotics10101245
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling and Biological Activities of Pleurotus columbinus Quél. Cultivated on Different Agri-Food Byproducts

Abstract: The genus Pleurotus (Fr.) P. Kumm (Pleurotaceae, Basidiomycota) comprises a cosmopolitan group of mushrooms highly appreciated for their nutritional value and health-promoting benefits. Despite there being many studies about the phytochemical composition of Pleurotus spp., there are very few reports dealing with the phytochemistry, antioxidant and antimicrobial activities of P. columbinus Quél. In this study, a mass spectrometry ultra-performance liquid chromatography mass spectrometry (UHPLC)-QTOF method, cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…This last sample also showed a moderate inhibition against Bacillus cereus , Pseudomonas aeruginosa , Staphylococcus aureus , and Candida albicans , despite a weak activity for the other samples. The antimicrobial properties of AM and AR samples agrees with the results of Selles et al [ 13 ], which found that a methanolic extract from A. pyrethrum aerial parts was able to inhibit S. aureus and B. cereus , despite slightly affecting E. coli and Pseudomonas aeruginosa ; however, the tested extracts showed lower potency, in terms of MIC values (µg/mL), compared to the reference drugs ciprofloxacin, fluconazole, and griseofulvin for the antibacterial and antifungal effects [ 40 ]. In fact, the MIC values of ciprofloxacin, fluconazole, and griseofulvin were always ≤4 µg/mL towards the tested bacterial and fungal strains [ 40 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This last sample also showed a moderate inhibition against Bacillus cereus , Pseudomonas aeruginosa , Staphylococcus aureus , and Candida albicans , despite a weak activity for the other samples. The antimicrobial properties of AM and AR samples agrees with the results of Selles et al [ 13 ], which found that a methanolic extract from A. pyrethrum aerial parts was able to inhibit S. aureus and B. cereus , despite slightly affecting E. coli and Pseudomonas aeruginosa ; however, the tested extracts showed lower potency, in terms of MIC values (µg/mL), compared to the reference drugs ciprofloxacin, fluconazole, and griseofulvin for the antibacterial and antifungal effects [ 40 ]. In fact, the MIC values of ciprofloxacin, fluconazole, and griseofulvin were always ≤4 µg/mL towards the tested bacterial and fungal strains [ 40 ].…”
Section: Discussionsupporting
confidence: 86%
“…The antimicrobial properties of AM and AR samples agrees with the results of Selles et al [ 13 ], which found that a methanolic extract from A. pyrethrum aerial parts was able to inhibit S. aureus and B. cereus , despite slightly affecting E. coli and Pseudomonas aeruginosa ; however, the tested extracts showed lower potency, in terms of MIC values (µg/mL), compared to the reference drugs ciprofloxacin, fluconazole, and griseofulvin for the antibacterial and antifungal effects [ 40 ]. In fact, the MIC values of ciprofloxacin, fluconazole, and griseofulvin were always ≤4 µg/mL towards the tested bacterial and fungal strains [ 40 ]. We have to consider that the extracts’ MIC values for the ethyl acetate samples were of the same order compared to the reference drugs, with values < 10 µg/mL, with regard to growth inhibitory effects against E. coli and T. rubrum species.…”
Section: Discussionsupporting
confidence: 86%
“…In light of all of the above, and based on our recent works, , we focused our attention on the genus Pleurotus and, specifically, on the Pleurotus ostreatus species characterized by a high economic significance. P.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the same extracts were assayed for the antifungal assays against different yeasts, dermatophyte, and fungal pool species: Candida albicans (YEPGA 6183), C. tropicalis (YEPGA 6184), C. albicans (YEPGA 6379), C. parapsilopsis (YEPGA 6551), Arthroderma crocatum (CCF 5300), A. curreyi (CCF 5207), A. gypseum (CCF 6261), A. quadrifidum (CCF 5792), A. insingulare (CCF 5417), A. quadrifidum (CCF 5792), Trichophyton mentagrophytes (CCF 4823), T. mentagrophytes (CCF 5930), T. rubrum (CCF 4933), and T. tonsurans (CCF 4834). Details are reported in our previous paper [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…P. Kumm. (Pleurotaceae, Basidiomycota) includes some of the main cultivated edible mushrooms in the world due to their gastronomic, nutritional, and medicinal properties, such as anti-inflammatory [ 1 ], antioxidant [ 2 , 3 ], antidiabetic [ 4 ], antitumor [ 5 ], and immunomodulating [ 6 ]. Due to their ability to improve protein content and quality, as well as the valuable health benefits of myco-chemicals or bioactive components present in these mushrooms [ 7 , 8 , 9 ], Pleurotus spp.…”
Section: Introductionmentioning
confidence: 99%